GPR182 is a novel marker for sinusoidal endothelial differentiation with distinct GPCR signaling activity in vitro - Schmid, Christian David; Schledzewski, Kai; Mogler, Carolin; Waldburger, Nina; Kalna, Viktoria; Marx, Alexander; Randi, Anna Maria; Géraud, Cyrill; Goerdt, Sergij; Reiners-Koch, Philipp-Sebastian (Biochemical and biophysical research communications, 2018)
Endothelial cells (EC) along the vascular tree exhibit organ-specific angiodiversity. Compared to most other ECs, liver sinusoidal endothelial cells (LSEC) that constitute the organ-specific microvasculature of the liver are morphologically and functionally unique. Previously, we showed that transcription factor Gata4 acts as a master regulator controlling LSEC differentiation. Upon analysis of the molecular signature of LSEC, we identified GPR182 as a potential LSEC-specific orphan G-protein coupled receptor (GPCR). Here, we demonstrate that GPR182 is expressed by LSEC and by EC with sinusoidal differentiation in spleen, lymph node and bone marrow in healthy human tissues. In a tissue microarray analysis of human hepatocellular carcinoma (HCC) samples, endothelial GPR182 expression was significantly reduced in tumor samples compared to peritumoral liver tissue samples (p=0.0105). Loss of endothelial GPR182 expression was also seen in fibrotic and cirrhotic liver tissues. In vitro, GPR182 differentially regulated canonical GPCR signaling pathways as shown using reporter luciferase assays in HEK293T cells. Whereas ERK and RhoA signaling were inhibited, CREB and Calcium signaling were activated by ectopic GPR182 overexpression. Our data demonstrate that GPR182 is an endothelial subtype-specific marker for human sinusoidal EC of the liver, spleen, lymph node and bone marrow. In addition, we provide evidence for GPR182-dependent downstream signaling via ERK and SRF pathways that may be involved in regulating endothelial subtype-specific sinusoidal differentiation and sinusoidal functions such as permeability.